Impact of predicting real-time clock corrections during their outages on precise point positioning - El-Mowafy, Ahmed (Maney Publishing, 2017)
Real-time precise point positioning (RT-PPP) is a popular positioning method for natural hazard warning systems (NHWS) such as for monitoring tsunami and earthquakes. PPP relays on the use of precise orbits and clock corrections. Hence, the positioning accuracy of RT-PPP will significantly deteriorate when experiencing a discontinuity in receiving these corrections, for instance due to a temporary modem failure. The best available approach in this case would be to use the International Global Navigation Satellite Systems Service ultra-rapid (IGU) orbits and clocks that would result in a low positioning accuracy. In this paper, we present a simplified approach to a method that we recently proposed to bridge outages in the corrections and improve the RT-PPP accuracy compared with the use of IGU. In this method, the most recent IGU orbits are used as they are compatible with the RT orbits; however, the clock corrections are predicted as a time series using a linear model with four sinusoidal terms. The prediction errors resulting from this method, age of the model and its validity period are discussed. The impact of using the proposed approach is evaluated at a number of sites of known positions by comparing its performance to using IGU orbits and clocks. Moreover, the impact of using predicted corrections is assessed in different scenarios. The experimental results proved validity of the presented approach where positioning mean RMSE of less than 20 cm was maintained during the outage period.